Antimicrobial Photodynamic Inactivation Using Topical and Superhydrophobic Sensitizer Techniques: A Perspective from Diffusion in Biofilms - Tonon, Caroline Coradi; Ashraf, Shoaib; Alburquerque, José Quílez; Souza Rastelli, Alessandra Nara; Hasan, Tayyaba; Lyons, Alan M.; Greer, Alexander (Photochemistry and photobiology, 2021)
This review describes nanoparticle and dye diffusion in bacterial biofilms in the context of antimicrobial photodynamic inactivation (aPDI). aPDI requires the diffusion of a photosensitizer (Sens) into the biofilm and subsequent photoactivation of oxygen for the generation of reactive oxygen species (ROS) that inactivate microbes. Molecular diffusion in biofilms has been long investigated, whereas this review is intended to draw a logical link between diffusion in biofilms and ROS, a combination that leads to the current state of aPDI and superhydrophobic aPDI (SH‐aPDI). This review should be of interest to photochemists, photobiologists and researchers in material and antimicrobial sciences as is ties together conventional aPDI with the emerging subject of SH‐aPDI. There is interest in photodynamic inactivation (aPDI), but it requires the diffusion of sensitizer into the biofilm. Several factors can affect the diffusion, including biofilm complexity, zeta potential, formal charge, and particle size. Superhydrophobic antimicrobial photodynamic inactivation (SH‐aPDI) is a promising method to inactivate biofilms due to its ability to deliver airborne singlet oxygen (1O2). Airborne 1O2 delivery via SH‐aPDI obviates the need for sensitizer penetration into the biofilm as opposed to aPDI which depends on topically applied sensitizer.